Provide assistance in preparing herbal fish to manage diseases and productivity in freshwater, collaborating with "KOPER BASAH.": Pendampingan pembuatan jamu ikan, untuk penanggulangan penyakit dan peningkatan produksi budidaya ikan air tawar bersama “KOPER BASAH” - hardi, Esti Handayani; Saptiani, Gina; Agustina, Agustina; Reynata, Ricko; Rahmah, Nur Rini; Jolpano, Andre (ANDIL Mulawarman Journal of Community Engagement, 2025)
The initiative to aid in the formulation of herbal medication for fish, targeting disease management and enhancing freshwater fish farming output alongside "KOPER BASAH," is implemented to instruct fish farmers in the creation of herbal remedies from indigenous flora for disease control in tilapia aquaculture. This activity involves detecting issues such as elevated death rates owing to pathogen assaults; facilitating the preparation of herbal medicine; assessing the efficacy of the produced herbal medicine; and monitoring and analyzing its impact on tilapia output. Knowledge pertaining to the signs of fish afflicted by infections and the management of diseased fish has augmented by 25-50%. Knowledge of plant kinds with antibacterial and immunostimulant properties increased by 30-50%, while abilities in herbal medicine preparation improved by up to 60%. This activity enhances the value of locally accessible raw materials and optimizes tilapia farming production in a secure, cost-effective, and sustainable manner. This research is anticipated to be a prudent advancement for the community in tilapia aquaculture by adhering to Good Aquaculture Practices and guaranteeing food safety of the resultant fisheries items.